Optimized Chitosan-Based Nanoemulsion Improves Luteolin Release - Camila Diedrich; Isabella C. Zittlau; Najeh M. Khalil; Adam F. G. Leontowich; Rilton A. de Freitas; Ildiko Badea; Rubiana M. Mainardes (MDPI AG, 2023)
Luteolin (LUT) is a flavonoid found in several edible and medicinal plants. It is recognized for its biological activities such as antioxidant, anti-inflammatory, neuroprotective, and antitumor effects. However, the limited water solubility of LUT leads to poor absorption after oral administration. Nanoencapsulation may improve the solubility of LUT. Nanoemulsions (NE) were selected for the encapsulation of LUT due to their biodegradability, stability, and ability to control drug release. In this work, chitosan (Ch)-based NE was developed to encapsulate luteolin (NECh-LUT). A 23 factorial design was built to obtain a formulation with optimized amounts of oil, water, and surfactants. NECh-LUT showed a mean diameter of 67.5 nm, polydispersity index 0.174, zeta potential of +12.8 mV, and encapsulation efficiency of 85.49%. Transmission electron microscopy revealed spherical shape and rheological analysis verified the Newtonian behavior of NECh-LUT. SAXS technique confirmed the bimodal characteristic of NECh-LUT, while stability analysis confirmed NECh-LUT stability when stored at room temperature for up to 30 days. Finally, in vitro release studies showed LUT controlled release up to 72 h, indicating the promising potential of NECh-LUT to be used as novel therapeutic option to treat several disorders.